BDNF Gene's Role in Schizophrenia: From Risk Allele to Methylation Implications - Fu, Xiaoqian; Wang, Jun; Du, Jianbin; Sun, Jing; Baranova, Ancha; Zhang, Fuquan (Frontiers in Psychiatry, 2020)
Background: Schizophrenia (SZ) is a severe chronic mental disorder with complex genetic mechanisms. Brain-derived neurotrophic factor (BDNF) is one of promising candidate genes for SZ, and rs6265 is a non-synonymous single nucleotide polymorphism (SNP) in BDNF. Methods: In this study, we conducted a case–control association study of rs6265 in a cohort of Han Chinese from east China, including 1407 SZ cases and 1136 healthy controls; and carried out a cis-mQTL (Methylation Quantitative Trait Loci) analysis for BDNF rs6265. Results: We detected a positive association of rs6265 with SZ (P = 0.037), with the minor allele (A) of rs6265 conferring a protecting effect for SZ (OR = 0.89). Furthermore, cis-mQTL analysis indicates that rs6265 is associated with several methylation loci surrounding BDNF. Conclusions: Together, our findings provide further evidence to support the involvement of BDNF gene in the genesis of SZ. Keywords: schizophrenia, BDNF, single nucleotide polymorphism, rs6265, methylation